A Selective Biligand Inhibitor of CK2 Increases Caspase‐3 Activity in Cancer Cells and Inhibits Platelet Aggregation. (26th September 2017) - Rahnel, Hedi; Viht, Kaido; Lavogina, Darja; Mazina, Olga; Haljasorg, Tõiv; Enkvist, Erki; Uri, Asko
Abstract: Cancer cells express high levels of CK2, and its inhibition leads to apoptosis. CK2 has therefore emerged as a new drug target for cancer therapy. A biligand inhibitor ARC‐772 was constructed by conjugating 4‐(2‐amino‐1, 3‐thiazol‐5‐yl)benzoic acid and a carboxylate‐rich peptoid. ARC‐772 was found to bind CK2 with a K d value of 0.3 nm and showed remarkable CK2 inhibitory selectivity in a panel of 140 protein kinases (Gini coefficient: 0.75 at c =100 nm ). ARC‐775, the acetoxymethyl ester prodrug of ARC‐772, was efficiently taken up by cells. Once internalized, the inhibitor is activated by cellular esterase activity. In HeLa cancer cells ARC‐775 was found to activate caspase‐3 (an apoptosis marker) at sub‐micromolar concentrations (EC50 =0.3 μm ), a 20‐fold lower extracellular concentration than CX‐4945, the only CK2 inhibitor under clinical trials. At micromolar concentrations, ARC‐775 was also found to inhibit ADP‐induced aggregation of human platelets. The overall results of this study demonstrate that oligo‐anionic biligand inhibitors have good potential for drug development. Abstract : True multitasking : Biligand inhibitors that may be developed into drug candidates or applied to study signaling pathways regulated by CK2 were constructed. Per‐esterification of inhibitor ARC‐772 [shown, K d(CK2) =0.3 nm ] supported intracellular uptake [shown, c  (in cells)=100 μm] . Relative to CX‐4945 (currently in clinical trials), ARC‐772 revealed higher cellular efficiency.